ANALISIS DAN EKSPLORASI KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF PADA MATERI BILANGAN CACAH DI SEKOLAH DASAR - Al Haniyah, Wafiqoh; Usman, Herlina; Nurhasanah, Nina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning in elementary schools still faces challenges, particularly in teaching whole numbers, due to students' low interest in learning and the limited use of interactive learning media. Learning activities are still dominated by lecture methods and simple instructional media, making it difficult for some students to understand place value concepts and write whole numbers correctly. This study aims to analyze the need for developing interactive multimedia learning media for whole numbers material in grade V elementary school. The study employed the analysis stage of the ADDIE development model using a descriptive qualitative approach. Data were collected through observation, interviews, and questionnaires administered to teachers and students at SDN Jatinegara 01. The findings indicate that although teachers have utilized learning media such as textbooks, worksheets, and PowerPoint presentations, the learning process remains less interactive and has not fully engaged students. Students showed strong interest in visual-based media, educational games, animations, and interactive learning activities. Therefore, the development of Microsoft PowerPoint-based interactive multimedia learning media is considered necessary to support students' understanding of whole number concepts and increase their learning motivation. This media is expected to create a more engaging, interactive, and meaningful learning experience for elementary school students.